2020
DOI: 10.23937/2378-3516/1410145
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Inhaled Nitric Oxide in Managing COVID-19 Associated Lung Complications Review of Literature

Abstract: The outbreak of novel coronavirus disease 2019 (COVID-19) in the city of Wuhan, Hubei Province, China, was declared a pandemic by the World Health Organization (WHO) on March 21, 2020. As of June 16, 2020, the World Health Organization (WHO) has reported near eight million cases and half a million deaths worldwide. The majority of cases have spontaneously resolved. However, some have developed various fatal complications including organ failure, septic shock, pulmonary edema, severe pneumonia, and Acute Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Off-label uses of NO include treatment of pulmonary hypertension and ARDS [113]. In addition, NO is effective against several bacteria, protozoa, and viruses [37]. Laboratory data have indicated that NO has antiviral activity due to its ability to induce IFN-gamma expression in macrophages [90].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
See 1 more Smart Citation
“…Off-label uses of NO include treatment of pulmonary hypertension and ARDS [113]. In addition, NO is effective against several bacteria, protozoa, and viruses [37]. Laboratory data have indicated that NO has antiviral activity due to its ability to induce IFN-gamma expression in macrophages [90].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…It also results in selective dilation of pulmonary vessels, improved arterial oxygenation, and reduced pulmonary hypertension. Ryan et al have recommended the use of NO for treatment of pulmonary arterial hypertension in hospitalized patients with COVID-19 [37,125].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%